Perspectives in philosophy, religion, and art : essays in honour of Margaret Chatterjee - Chatterjee, Margaret, 1925-; Balasubramanian, R. (Rajangam), 1929-; Thomas, V. C. (New Delhi : Indian Council of Philosophical Research : Distributed by Munshiram Manoharlal Publishers, 1993)
Contributed articles.
Includes bibliographical references.
Keywords: Philosophy; Philosophy and religion